Basic Facts About the United Nations - United Nations (New York United Nations Publications, 1998)
This new, updated edition of Basic Facts about the United Nations reflects the multitude of ways in which the United Nations touches the lives of people everywhere. It chronicles the work of the Organization in such areas as peace, development, human rights, humanitarian assistance, disarmament and international law. In describing the work of the United Nations family of organizations, this book provides a comprehensive account of the many challenges before the international community, as well as the joint ongoing efforts to find solutions.
Keywords: Politics; International relations; Nonfiction; History; Reference